Application of extended artificial physics optimisation in product colour harmony design. (2016) - Yang, Gangjun; Zhang, Xueliang
There exists large blindness in computer-aided colour harmony design. To pursue a better design scheme of the product colour with the proposition for emotional, a model of product colour harmony design with colour emotion is established according to the quantitative affiliation relations between colour emotional and colour property. In the model, the designer should determine the value domains of three colour properties of the main colour and secondary colours according to the colour emotional expressed by products. The value domain is the feasible region of the main colour and secondary colours, which are regarded as the constrained conditions. And the aesthetics measure in the objective function will be optimised. An extended artificial physics optimisation (EAPO) algorithm adds the personal best positions of all individuals in the artificial physics optimisation's (APO) force computation equation, which can provide much useful information for the search and improve the convergence velocity of APO. EAPO algorithm is employed to search the best aesthetics measure in the colour feasible regions. The example simulation shows the effectiveness and efficiency of the method.